TEPUNG REBUNG TERMODIFIKASI SEBAGAI SUBSTITUEN TERIGU PADA PEMBUATAN DONAT KAYA SERAT - Meta Haryani; Lina Widawati; Eva Ramalia Sari (UNIVED Press, Universitas Dehasen Bengkulu, 2014)
Bamboo shoots are the young shoots that grow from the roots of bamboo. Besides being used as the contents of spring rolls, bamboo shoots are also frequently used as a vegetable for the Central Javanese cuisine. The purpose of this study was to characterize the properties of fiber-rich donut made from modified bamboo shoots flour. The study begins with a modified bamboo shoots processing with treatment variations of fermentation time, which is 3 days and 5 days. The next stage is the processing of modified bamboo shoots donuts substitution with treatment comparisons of flour and bamboo shoots as much as 400 : 100 grams, 300 : 200 gr and 200 : 300 gr. Analysis is conducted for ash content analysis and analysis of the level of preference parameters panelists for color, flavor and texture. Ash content measurement results showed that there was no significant difference in treatment 3 days of fermentation, where as the fermentation time at 5 days of treatment, the results showed that the more flour modified bamboo shoots flour are used, the greater the ash content donuts. A test showed that the donut panelists favored treatment comparison flour and bamboo shoots as much as 400 : 100 gr and 300 : 200 gr and ferment for 3 days.Keywords: bamboo shoots, modified bamboo shoots flour, doughnut